1977
DOI: 10.2172/7219229
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional analysis of solids transport and dispersion in a rotary kiln

Abstract: NOTICE This document contains information of a preliminary nature. It is subject to revision or correction and therefore does not represent a .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There have been many reports on the amoeboid plastids. The studies on the development of plastids in the leaves of Phaseolus vulgaris and Zea mays supposed that the amoeboid form represented the transition of the proplastid from a plastid stage to that of a chloroplast (Whatley 1974, 1977, 1983b, c, Thomson and Whatley 1980. The studies on development of plastids in the roots of Phaseolus vulgaris and Azolla indicated that the transition was an expression of a spatial sequence of plastid differentiation along the root axis from its tip to more mature regions Gunning 1981, Whatley 1983a).…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports on the amoeboid plastids. The studies on the development of plastids in the leaves of Phaseolus vulgaris and Zea mays supposed that the amoeboid form represented the transition of the proplastid from a plastid stage to that of a chloroplast (Whatley 1974, 1977, 1983b, c, Thomson and Whatley 1980. The studies on development of plastids in the roots of Phaseolus vulgaris and Azolla indicated that the transition was an expression of a spatial sequence of plastid differentiation along the root axis from its tip to more mature regions Gunning 1981, Whatley 1983a).…”
Section: Discussionmentioning
confidence: 99%